2020
DOI: 10.15414/jmbfs.2020.10.3.467-473
|View full text |Cite
|
Sign up to set email alerts
|

Garlic-Ginger as Potential Bio-Preservative in Fermented Maize and Sorghum Pastes

Abstract: Garlic and ginger are natural spices with potentials as biopreservatives and allied health benefits. Fermented pastes either from maize or sorghum have a shelf life of fewer than 10 days except when refrigerated. In this study, garlic and ginger were added separately and in combinations to the fermented pastes prepared from maize and sorghum grains with a view to extending its shelf life resulted in 7 treatments. During storage for 4 weeks at ambient and refrigeration temperatures, the microbial load was enume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The methods described in the Fig. 1 ∼ 4 for production are simple, cost effective, require simple equipment, no special starter culture, no chemical added are still practice in many Nigerian suburban households, cultures, and ethnic affiliations ( Adepoju et al, 2016 ; Olasupo et al, 2016 ; Adesulu-Dahunsi et al, 2017 ; Oyeyinka et al, 2019 ; Olaniran et al, 2020a , 2020b ).…”
Section: Biotechnology and Pro-technology In Food Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…The methods described in the Fig. 1 ∼ 4 for production are simple, cost effective, require simple equipment, no special starter culture, no chemical added are still practice in many Nigerian suburban households, cultures, and ethnic affiliations ( Adepoju et al, 2016 ; Olasupo et al, 2016 ; Adesulu-Dahunsi et al, 2017 ; Oyeyinka et al, 2019 ; Olaniran et al, 2020a , 2020b ).…”
Section: Biotechnology and Pro-technology In Food Productionmentioning
confidence: 99%
“…Fermentation facilitates not only the preservation of foods but also their biochemical modulation for enhanced health and nutritional benefits coupled with profound organoleptic quality improvement. This process affords spatial requirements conducive for the proliferation of useful beneficial microbes and the competitive exclusion of harmful species capable of causing spoilage coupled with value depreciation of the food ( Olaniran et al, 2020a ). Daly et al (1996) , Raman et al (2014) , and Olaniran et al (2020b) reported that derivatives from the process in the form of organic substances facilitate food preservation and generation of distinctly novel products important for improving food quality and safety.…”
Section: Trends In the Application Of Microorganisms In Food Producti...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some volatile compounds which are responsible for antimicrobial activities in ginger were ápinene, borneol, camphene, and linalool [116]. The presence of ginger in Pekasam may help inhibit the growth of bacteria like Bacillus, Flavobacterium, Leuconostoc, Proteus, Salmonella, Staphylococcus and Streptococcus [117]. Reference [118] proved that 2% (w/w) ginger could reduce the total viable count (TVC) of tomato paste from 13.45 log cfu/g to 11.54 log cfu/g at the 8th week of storage.…”
Section: Antimicrobial Function Of Spices In Improving the Quality Of...mentioning
confidence: 99%
“…Micronutrient deficiencies have become a foremost health concern due to constrained diversity of inexpensive nutritious food thus limiting dietary diversity among indigents. [1][2][3] The United Nations Inter-agency Group for Child Mortality Estimation 4 has revealed high risks of blindness and recurrence of measles, diarrhea, and sometimes death of children, pregnant women, and vulnerable groups around the world because of diets. Inter-communal violence is on the increase in Nigeria and children are believed to constitute more than half (58%) of the internally displaced population.…”
Section: Introductionmentioning
confidence: 99%